Significance of basal-most leaf anatomy in taxonomy of Gagea (Liliaceae): a study of species from Kurdistan, Iraq - Ezamakhshi, Bakhtyar Abdalla Mohammed; Faghir, Marzieh Beygom; Zamani, Asghar (Phytotaxa, 2025)
In this study, anatomical characteristics of the basal-most leaf of 11 species of the Gagea from the Kurdistan region of Iraq were assessed. To assess the value of quantitative and qualitative variables in describing the interspecific and intersectional relationships, factor analysis of mixed data (FAMD) analysis was performed followed by a hierarchical clustering on principal components (HCPC). The results showed that the basal-most leaf anatomical features were taxonomically informative and can be used as important criteria for the delimitation of sections and species of the genus. Some characters of the basal leaf, in particular the shape, apex, presence and number of angular collenchyma bundles, width of the leaf blade and thickness of the upper and lower epidermis, were of value for the differentiation of the studied taxa. Finally, an identification key was established on the basis of these anatomical characteristics.